Microscopic Response of Limestone Physical Deterioration under Water-Rock Alternation in the Acidic Environment - Wei Liang; Ke Li; Jiashun Luo; Mengtang Xu; Fushou Feng (Geofluids)
In order to investigate the microscopic response mechanism of limestone deterioration under alternating water-rock action in the acidic environment, the porosity, water absorption, mass loss characteristic, and microcrack propagation characteristic were analyzed by laboratory wetting-drying cyclic tests. The results show that, with increasing the number of cycles, the porosity, water absorption, and mass deterioration of the limestone specimens showed an overall increasing trend; moreover, at the beginning of the cycles, the physical deterioration of the specimen was significantly affected by the wetting-drying cycles, and at the end of the cycles, the physical deterioration of the specimen tended to be stable. The porosity deterioration degree reached 30.324% at the beginning of the cycles; there is a slight fluctuation in 20 cycles and then decreases as the number of cycles increases. The growth rate of water absorption increases slowly in 5~15 cycles and reaches the peak value in 20 cycles, and the growth rate decreases rapidly in the latter stages of the cycles. The increase rate of mass deterioration degree decreases with the increase of cycle number, the maximum average value can reach 61.887% at the beginning of cycles and is relatively stable at 20~25 cycles, and the average value at the end of cycle is obviously reduced by 3.167%. The nuclear magnetic resonance (NMR) test shows that the number and size of pores in the rock gradually increase with the increase of the number of wetting-drying cycles, and the wetting-drying cycles aggravate the internal damage of the rock. The number of shear cracks and fragmentation of the specimens increase as the increase of the number of cycles, and the failure of the specimens is mainly in the form of shear damage in the uniaxial compression test.